1983
DOI: 10.1128/mcb.3.3.421
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of simian virus 40 tumor antigens to virus-induced mutagenesis.

Abstract: We analyzed the mutation frequency to 8-azaguanine (8AZ) resistance in rat FR3T3 cells acutely infected with simian virus 40 wild type and tsA and early deletion mutants and in a series of temperature-sensitive (N) and temperatureinsensitive (A) transformants derived from Chinese hamster lung (CHL) cells. Upon acute infection, the frequency of mutation to 8AZ resistance was raised at most by two-to eightfold over the spontaneous frequency, and it was independent of the presence of a functional 90,000-molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1986
1986
1992
1992

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Investigators have reported no mutagenic effect of SV40 in some experiments and 12-fold or greater increases in the frequency of mutants in other experiments. Conflicting results have been obtained regarding the role of T antigen in SV40-mediated mutagenesis (13,(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Investigators have reported no mutagenic effect of SV40 in some experiments and 12-fold or greater increases in the frequency of mutants in other experiments. Conflicting results have been obtained regarding the role of T antigen in SV40-mediated mutagenesis (13,(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous report, we made use of the XC cell line, which is not permissive for HSV-2, to demonstrate that intact viral particles could increase the frequency of HPRT-mutants by factors ranging from 2.4 to 10.3 (38). Other DNA viruses such as simian virus 40 and adenovirus type 2 can cause mutations at several loci in nonpermissive infections (14,27,28,50,52,60). However, the nature of the virally induced mutations has not been systematically studied at the molecular level, and the mutational mechanism of these viruses is not known.…”
mentioning
confidence: 99%